2014
DOI: 10.2147/ott.s67998
|View full text |Cite
|
Sign up to set email alerts
|

Proapoptotic and antiinvasive activity of Rac1 small molecule inhibitors on malignant glioma cells

Abstract: Malignant gliomas are characterized by an intrinsic ability to invade diffusely throughout the normal brain tissue. This feature contributes mainly to the failure of existing therapies. Deregulation of small GTPases signaling, in particular Rac1 activity, plays a key role in the invasive phenotype of gliomas. Here we report the effect of ZINC69391, a specific Rac1 inhibitor developed by our group, on human glioma cell lines LN229 and U-87 MG. ZINC69391 is able to interfere with the interaction of Rac1 with Doc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 39 publications
2
33
0
Order By: Relevance
“…IA-116 demonstrated higher antiproliferative potency than its parental compound in metastatic breast cancer cells, and decreased metastasis to the lung by 60% in an in vivo model of experimental metastasis (Cardama et al, 2014a). Also, IA-116 reduced cell proliferation and invasion in other cancer types, such as leukemia and glioma (Bouquier et al, 2009;Cardama et al, 2014b). In another study, treatment with 1A-116 reverted therapy resistance to tamoxifen in breast cancer cells (Gonzalez et al, 2017), demonstrating the therapeutic potential of Rac inhibitors in overcoming therapy resistance.…”
Section: Targeting Vav1/2/3mentioning
confidence: 97%
“…IA-116 demonstrated higher antiproliferative potency than its parental compound in metastatic breast cancer cells, and decreased metastasis to the lung by 60% in an in vivo model of experimental metastasis (Cardama et al, 2014a). Also, IA-116 reduced cell proliferation and invasion in other cancer types, such as leukemia and glioma (Bouquier et al, 2009;Cardama et al, 2014b). In another study, treatment with 1A-116 reverted therapy resistance to tamoxifen in breast cancer cells (Gonzalez et al, 2017), demonstrating the therapeutic potential of Rac inhibitors in overcoming therapy resistance.…”
Section: Targeting Vav1/2/3mentioning
confidence: 97%
“…In fact, it is highly conserved in other members of the Rho GTPase family of proteins, such as Rac2/3 and RhoA/B/C/D/G (Haeusler et al, 2003). 1A-116 Rac1 inhibitor showed antitumoral activity in vitro on a wide variety of cancer types such as breast cancer (Cardama et al, 2014a;Gonzalez et al, 2017), glioblastoma (Cardama et al, 2014b) and acute myeloid leukemia (Cabrera et al, 2017). In this regard, we have already reported that 1A-116 has a profound effect on proliferation, migration, invasion, metastasis, apoptosis, and cell cycle arrest.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of cytoskeleton-associated proteins and pathways involved in glioma has also been reported in numerous previous studies ( 27 , 28 ). In addition, increasing evidence revealed that lncRNAs are associated with the occurrence and development of glioma by regulating the structure of reorganization of cytoskeleton-associated proteins and signaling pathways ( 29 , 30 ). Additionally, the association between metastasis or cytoskeleton and the prognosis of glioma has also been reported ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%